A comparison of anthropometric and functional profile of walking practioners, from Maringa in 1999 and 2000 - Celso Souza; Darlei Landi; Roberto Macoto Miazaki; Adriane Poliseli; Ana Paula Alcantara; Alexandra Gimenes; Melissa Saporski Alves Nunes (Journal of Physical Education (Maringá), 2008)
This study aimed at comparing the anthropometric and functional profile of walking practitioners from Maringá city in 1999 and 2000, as well as correlating the V02 max and Kline Test, fat percentage, absolute fat, thin mass and Body Mass Index (BMI). It is a descriptive research which included 71 male and 97 female subjects in 1999, and in 2000 it involved 75 male and 91 female subjects. The data were collected through the use of an anamnesis form, Filizola scales, a Cescorf plicometer, a tape measure, a polar frequencymeter and the application of Kline's mile test. The data were applied in the 4.0 Sapat software. We can conclude that there were no significant changes in the walkers profile during 1999 and 2000. Concerning the correlation of V02 max. and the previously mentioned variants, we conclude that there was a negative linear correlation for the thin mass, for both sexes, in 1999, and for the thin mass and absolute fat, in the male group in 2000.